(untitled) (Journal of Informatics Education and Research, 2025)
This paper studies the role of foreign exchange markets in determining the value of the Indian Rupee, focusing on the macro and microeconomic factors within India’s managed floating exchange rate regime. The study is based on traditional determinants—such as interest rate differentials, inflation, and growth—, which interact with short-term speculative forces, global oil prices, and changes in U.S. Federal Reserve policies. With a contingent list of the use of various quantitative tools, mainly regression analysis, this paper evaluates the impact of key economic variables like the repo rate, inflation, government spending, and public debt on the INR-USD exchange rate. They further analyze the influence of globalization, geopolitics, and international trade policies that outline how U.S. monetary policy, along with fluctuations in global oil prices, affect India’s balance of trade and currency stability. The reserve bank of India through foreign exchange intervention manages currency volatility. The study provides useful insights for policymakers and stakeholders to navigate currency fluctuations in an increasingly globalized financial system through an analysis of historical trends in foreign reserves, current account deficits, and commodity prices.